Uji Toksisitas Ekstrak Kulit Buah Tanaman Jeruk Purut (Citrus hystrix DC.) Dengan Menggunakan Metode Brine Shrimp Lethality Test (BSLT) - Isti Aprilyanie; Virsa Handayani; Rezki Amriati Syarif (Makassar Natural Product Journal (MNPJ), 2023)
Kaffir lime peel extract (Citrus hystrix DC.) contains flavonoids and alkaloids still rarely used as medicine; however, its toxicity is lack of the research until now. The research aimed to determine the effects of toxicity in the extracts by Brine Shrimp Lethality test (BSLT). The extraction used maceration and infusion. The former used ethanol of 70% with the thick extract of 3.81 mg and the letter used aquadest with the dried extract of 2.77 mg. The screening-was conducted by observing the color change in the extract and obtained the toxicity effects at the concentration of 1 ppm, 3 ppm, 5 ppm, 7 ppm, and 9 ppm by obtaining LC50 values for both the ethanol extract of 0.98 ppm and water extract of 1.20 ppm. The results showed that the water and ethanol extracts of kaffir lime peel had toxic properties.